Pengaruh Nilai Sukuk, Rating Sukuk, Risiko Sukuk, dan Likuiditas Terhadap Yield Sukuk pada Perusahaan yang Menerbitkan Sukuk - Putri, Yola Yunita; Harkaneri, Harkaneri; Djamil, Nasrullah (Basecamp Economics PubMed, 2024)
Sukuk yield is a measure of the return that sukuk investors will receive at maturity. The purpose of this study was to determine the partial and simultaneous influence between sukuk value, sukuk rating, sukuk risk, and liquidity on sukuk yield in companies that issue sukuk in the Indonesian Stock Exchange (IDX) 2023. The data used in this study are secondary data. The sample withdrawal in this study was purposive sampling. This research is descriptive quantitative using multiple linear regression test tools and using the SPSS V.27 data processing program. The corporate sukuk studied in this study are sukuk mudharabah listed on the Indonesia stock exchange. In this study, based on the t test conducted, it shows that the variables of Sukuk Value, Sukuk Rating, and Sukuk Risk have a significant effect on sukuk yield. While Liquidity has no significant effect on sukuk yield. Through the F test it is known that together the independent variables affect the dependent variable. Determination in this study amounted to 0.767, meaning that the independent variables in this study have a strong influence of 76.7% on sukuk yield. While the remaining 23.3% is influenced by other variables outside this study.